Chinese Engagement in Africa Drivers, Reactions, and Implications for U.S. Policy - Hanauer, Larry (RAND Corporation, 2014)
Examines Chinese engagement with African nations, focusing on (1) Chinese and African objectives in the political and economic spheres and how they work to achieve them, (2) African perceptions of Chinese engagement, (3) how China has adjusted its policies to accommodate African views, and (4) whether the United States and China are competing for influence, access, and resources in Africa and how they might cooperate in the region.